2008
DOI: 10.1002/adsc.200700464
|View full text |Cite
|
Sign up to set email alerts
|

A Stereoselective Palladium‐Mediated Reductive Coupling of Electron‐Deficient Terminal Iodoalkenes

Abstract: Iodoacrylate esters undergo palladiumcatalysed reductive homocoupling to derive dienyl diester derivatives. This reductive coupling can be extended to ester-substituted terminal iododienes to derive tetraene diesters. In all cases, the reactions show relatively high levels of stereocontrol, which shows an inversion of stereochemistry about one iodoalkene unit. This process, and the suggestion that the reaction releases diiodine, is consistent with a syn-1,2-addition of an iodopalladium(II)-alkene species acros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 47 publications
1
5
0
Order By: Relevance
“…The isolated products 8 were identified by 1 H and 13 C NMR analysis. The NMR data well agree with the reported data (8a [31], 8b [32], 8c [33] …”
Section: General Procedures For Hydrostannylation Of Alkynes Followed supporting
confidence: 91%
“…The isolated products 8 were identified by 1 H and 13 C NMR analysis. The NMR data well agree with the reported data (8a [31], 8b [32], 8c [33] …”
Section: General Procedures For Hydrostannylation Of Alkynes Followed supporting
confidence: 91%
“…As previously reported, 3c the benefit of using tri(o-tolyl)phosphine was primarily to provide steric bulk around the palladium(II) intermediate species, in order to prevent competitive iodide homocoupling. 5 We have already mentioned that this substrate does not undergo reductive dimerisation, which seems more likely to do with the difficultly in adding palladium across an aromatic double bond rather than any steric differences, and hence, because…”
Section: Synthesis Of Dienyliodidementioning
confidence: 99%
“…It should be noted that the HM reactions of iodide 5 are non-trivial due to competition from the competing reductive dimerisation side-reaction. 5 Indeed, we have previously reported that employing tri(o-tolyl)phosphine is one of the few ways of suppressing this reaction. 3c The results of these studies were not initially promising (see Table 1), since the use of the standard conditions developed especially for the coupling of iodide 5 with vinylboronate esters 3c were highly inefficient (Table 1, Entry 1), resulting in a low yield of the desired product 13.…”
Section: Synthesis Of 3-methyl-3-vinylcyclopentanone 12mentioning
confidence: 99%
“…[85] Later, based on the selectivity problems raised by these total syntheses, a methodology for reductive dimerisation was developed that used electron-deficient terminal iodoalkenes and polyenes. [86] In a second generation synthesis, a Heck reaction instead of a Sonogashira cross-coupling reaction (see section 2.10) was applied by Kirschning, where key fragments 96 and 97 were joined to achieve the synthesis of thuggacin derivatives (Scheme 35). [87] Selecting the Heck reaction over the Sonogashira coupling was driven by difficulties found during a C13-C14 alkyne selective reduction.…”
Section: Heck Reactionsmentioning
confidence: 99%